The Role of Funeasylearn Application in Learning English Vocabulary - Nurfalah, Hana (Papanda Journal of English Education, 2025)
Vocabulary is one of the important components in English. As a component of language. learning vocabulary is necessary because the more words students know, the better the chance to understand them. But, the students still difficult to learn English vocabulary. The difficulties come from some factor, such as: intrinsic or extrinsic. Faced with this situation, researcher use learning media to support the students in learning English vocabulary. In the current digital era, media has become an important component in the education system. Learning media offers innovative and effective methods to improve student in understanding english vocabulary. One Learning media can be used is mobile-application the FunEasyLearn app. The purpose of this study is to explain how do students' use the FunEasyLearn application in learning English vocabulary and to find out the students' perceptions after using the FunEasyLearn app in learning English vocabulary. The method used in this research is qualitative method. Data collection techniques was done by using observation and interviews on the topic of students perceptions of the usefulness and effectiveness of FunEasyLearn app. Data analysis techniques was done by using thematuc analysis. The participants in this research is students junior high school. The results in this study, that FunEasyLearn app easy to use and then most of the students' perceptions were positive and feel happy, because by using FunEasyLearn app find: (1) Effective tool learning media; (2) interest; (3) motivation; (4) mastery English vocabulary; and (5) To help/support the students in learning English vocabulary (to write, speak, listen, read). In conclusion, the FunEasyLearn app has plays role in learning English vocabulary.